2008
DOI: 10.1149/1.2909552
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscaled (La[sub 0.5]Sr[sub 0.5])CoO[sub 3−δ] Thin Film Cathodes for SOFC Application at 500°C<T<700°C

Abstract: Nanoscaled and nanoporous ͑La 0.5 Sr 0.5 ͒CoO 3−␦ ͑LSC͒ thin film cathodes ͑film thickness ranging from 200 to 300 nm, grain and pore size in the range of 50 nm͒ were electrochemically characterized to determine their potential for intermediate and lowtemperature solid oxide fuel cells ͑SOFCs͒. Chemically homogeneous, large area ͑25 cm 2 ͒, and nanoporous LSC thin films were derived from metallorganic precursors ͑metallorganic deposition͒ and deposited on yttria-doped zirconia ͓͑YSZ͒ "design 1"͔ and gadolinia-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
141
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(145 citation statements)
references
References 51 publications
4
141
0
Order By: Relevance
“…Indeed, some attempts have been already reported on the development of pure oxide-based electrodes for fabricating fully-ceramic µSOFC, based on state-of-the-art materials on bulk SOFC systems working as cathodes [19][20][21][22][23][24][25][26][27] or anodes [28]. However, only few results have been reported on µSOFC performance using ceramic electrodes [29][30][31][32].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Indeed, some attempts have been already reported on the development of pure oxide-based electrodes for fabricating fully-ceramic µSOFC, based on state-of-the-art materials on bulk SOFC systems working as cathodes [19][20][21][22][23][24][25][26][27] or anodes [28]. However, only few results have been reported on µSOFC performance using ceramic electrodes [29][30][31][32].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Other common cathode materials in micro-SOFCs with operating temperatures of below 600°C are ABO 3 perovskites, such as mixed conducting lanthanum strontium cobalt (LSC) oxide [59][60][61], lanthanum strontium cobalt iron oxide (LSCF) [62][63][64][65][66] and barium strontium cobalt iron oxide (BSCF) [67][68][69]. Most of the studies reported so far in the literature on cathodes for micro-SOFCs essentially focus on the investigation of oxygen reduction mechanisms with geometrically well- Fig.…”
Section: Electrodesmentioning
confidence: 99%
“…(IT-SOFCs) [9] [10]; these may be achieved by either reducing the thickness of the electrolyte which reduces its ohmic resistance [11] [12] [13], developing new electrodes with improved catalytic activities which reduce overpotential [14] [15] [16] [17] or improving the electrode microstructure which increases the electrochemical reaction area [3] [18] [19].…”
Section: Introductionmentioning
confidence: 99%